Avaliação do desempenho de misturas asfálticas porosas modificadas com politereftalato de etileno (PET) - Queiroz, Bismak Oliveira de (2016)
The accumulated water on pavement surfaces is one of the factors responsible for the occurrence of traffic accidents, as it reduces the tire-pavement interface friction. The use of porous asphalt mixtures can increase road safety because it increases the adherence between a vehicle's tires and the pavement, especially in a wet highway, owing to its high drainage capacity. Accordingly, this research had the purpose of analyzing the use of polyethylene terephthalate (PET) waste as an alternative of additives to porous asphalt mixtures. The work method consisted of materials characterization, determination of the optimum binder content, production of three kinds of asphalt mixtures (conventional, with the addition of PET, and with polymer asphalt) and the performance of draindown tests, moisture susceptibility, resilient modulus, flow number, fatigue test, permeability to the asphalt mixtures, in their respective optimum binder contents. The PET was added to the mixtures by a dry process in the proportions of: 0; 0,33; 0,5; 0,75 e 1% regarding to the weight of the aggregates. The asphalt mixtures with polymer asphalt were taken as reference. Considering the mixtures design, additions of 0,75% PET up carried out the lowest optimum binder content. Besides that, the addition of PET contributed for a binder draindown inhibition and improved the mixtures performance regarding to moisture susceptibility. The PET additivated mixtures presented an increasing in the resilient modulus and a tendency of a longer fatigue life at low tension levels and high number of load applications. However, the mixtures are susceptible to rutting, even though presenting stiffening. Concerning to permeability, the execution of only one test became inconclusive. Although, it was verified that PET can present viability of being used as additive porous asphalt mixtures.